www.gamevibes.com.br: a trilha sonora nos games - Salles, Lucas [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research is the creation of an on-line multimedia product, more specifically a blog. We will analyze the specific cultural content that will treat this research: the soundtrack in games as journalistic informative content. To do this we develop a site in WordPress® platform, creating from visual identity, such as layout, logo, color distribution and texts, etc. as well as extensive research on the subject that is the focus of the blog, titled GAME VIBES® Soundtracks. A growing team initially composed of two editors and three employees, will power the site. The members will be responsible for collecting information to create items in the site that have information or opinionated character, respecting the theories of specialized cultural journalism for the web

O presente trabalho consiste na criação de um produto multimídia on-line, mais especificamente um blog. Analisaremos o conteúdo cultural especifico que trataremos nesta pesquisa: a trilha sonora nos games como conteúdo informativo jornalístico. Para isso vamos desenvolver um site na plataforma WordPress®, criando desde a identidade visual, como layout, logomarca, distribuição de cores e textos, etc. além de uma ampla pesquisa acerca do assunto que é foco do blog, intitulado GAME VIBES® Soundtracks. O site será alimentado por uma equipe crescente, composta inicialmente por dois editores e três colaboradores. Os integrantes serão responsáveis por coletar informações para criar os artigos do site que terão caráter informativo ou opinativo, respeitando as teorias do jornalismo cultural especializado para a web
Keywords: Jornalismo eletrônico; Sites da Web - Desenvolvimento; Cultura; Jogos; Blogs; Online journalism